Covid-19: A Review of the Relentless Pandemic Ever - Srivastava, Mohit Kishore; Kumar, Dileep; Jauhari*, Sugandha; Gupta, Anil Kumar; Mishra, Sudhir Ram Kishore; Yadav, Ganesh (International Journal of Innovative Research in Medical Science, 2020)
This article highlights key facts about the recent ongoing relentless pandemic of SARS-COV2 virus causing the disease COVID 19.On 31 December 2019, WHO was alerted to a cluster of pneumonia patients in Wuhan City, Hubei Province of China. WHO first declared it as a Public Health Emergency of International Concern (PHEIC) under International Health Regulations (2005) on 30th January and finally it was designated as “Pandemic” on 11th March 2020 when majority of European countries, western pacific region, region of America and south-east Asia was adversely affected. The pandemic has caused almost 20 lakh confirmed cases globally with 1,23,000 deaths making it one of the worst pandemics of this time. The developed countries have been adversely affected with massive load on their health care system and unavailability of proper protective equipment’s for the frontline workers followed by unavailability of any vaccine or treatment for this disease. Social distancing, Hand hygiene and wearing masks seem to be the most effective preventive measure to contain the virus. Due to this both the developing and developed countries have undergone complete lockdown to prevent further transmission of virus.